Anemia in Pregnant Women Correlated with The Estimated Fetal Weight - Ratna Puspita Sari; Susanti Pratamaningtyas; Dwi Estuning Rahayu (Journal of Ners and Midwifery, 2024)
During pregnancy, the body's need for oxygen increases, causing an increase in erythropoietin production. An increase in plasma volume has an effect on fluid retention and blood dilution in pregnancy, causing a decrease in hematocrit, causing a decrease in Hb concentration and causing anemia. One possible impact is hampering fetal growth and development. The development of the fetus in the womb can be monitored by estimating the fetus's weight to detect fetal growth abnormalities early. This study aimed to understand the correlation between anemia in pregnant women and estimated fetal weight in the working area of the Sambi Health Center, Kediri Regency. The design of the study was cross-sectional, with a sample of 34 pregnant women with anemia. The sampling technique applied consecutive sampling. The instruments of the study were met line, Sysmex hematology analyzer and observation sheet. The results of this study were analyzed using the Kendall Tau test, and obtained a ρ value of 0.03˂α 0.05, namely H0 was rejected so that there was a correlation between anemia in pregnant women and the estimated weight of the fetus in the working area of the Sambi Community Health Center, Kediri Regency. When a pregnant woman experiences anemia, it results in disturbances in metabolism and exchange of substances in the tissues, then the placenta shrinks, resulting in a decrease in the transfer of important nutrients for the growth and development of the fetus. The impact of this situation is a slowdown in fetal growth which results in a low estimated fetal weight.